The Future of the Local Broadcasting Industry Post-PolicyAnalog Switch Off - Rakhmaniar, Almadina; Slamet, Adiyana (JIPSI Jurnal Ilmu Politik dan Komunikasi, 2025)
The Job Creation Act (Undang-Undang Cipta Kerja) Number 11 of 2020 has mandated the Analog Switch Off (ASO) program to be carried out no later than November 2, 2022 at 24.00. Analog Switch Off is part of the process of digitalization of broadcasting, which is the process of switching or migrating terrestrial television national television that was originally analog broadcast into digital broadcast. This ASO Program will significantly impact various aspects of the broadcasting industry, including local television stations. Based on this, this study aims to determine how the implementation of the Analog Switch Off program affects the local broadcasting industry, especially local broadcasters or local television stations, and how the future of the local broadcasting industry after the implementation. The study used qualitative methods with a descriptive approach and library research. The results of the study stated that the implementation of the ASO Program has significantly impacted the local broadcasting industry, namely changes in business models, improved broadcast quality, and understanding of changes in viewer behavior.